2020
DOI: 10.1016/j.heliyon.2020.e05232
|View full text |Cite
|
Sign up to set email alerts
|

Variation of HLA class I (-A and -C) genes in individuals infected with hepatitis B or hepatitis C virus in Cameroon

Abstract: The Human Leucocyte Antigens (HLA) work in concert with other immune factors to modulate immunity to viral infections. Extensive variation has been reported in the genetic sequences and functions of classical HLA class I genes in many (mostly Western) populations, and several HLA associations with infectious disease outcomes have been reported. Little is known about their role in the susceptibility or resistance to hepatitis viruses in Central African populations. The aim of this study was to determine variant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 50 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…HLA-C has been widely studied for its pivotal role in the immune cellular response to viral infections. Previously published studies linked specific HLA-C variants to HPV-related cervical disease [ 27 ] to patients chronically infected by HCV [ 28 ] and by HBV [ 29 ]. The focus of this work was to determine whether there was an association between HLA-C variants’ stability and HIV-1 infection control.…”
Section: Discussionmentioning
confidence: 99%
“…HLA-C has been widely studied for its pivotal role in the immune cellular response to viral infections. Previously published studies linked specific HLA-C variants to HPV-related cervical disease [ 27 ] to patients chronically infected by HCV [ 28 ] and by HBV [ 29 ]. The focus of this work was to determine whether there was an association between HLA-C variants’ stability and HIV-1 infection control.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, HLA-B*35:14 was observed to be a weak binder for both 9-mers at Pos 30 and Pos 29. The previous study has shown that HLA-C*04:01 is one of the most frequent HLA class I alleles in Cameroonian infected with HBV, with a frequency of 37.5% in patients with HBV compared with that of 25.5% in healthy populations ( Yengo et al, 2020 ). In addition, HLA-C*04:01 was also observed to be in association with poor viral control of HIV ( Olvera et al, 2015 ) and severe clinical course of COVID-19 ( Weiner et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since HLA-A*23 is associated with lower VRC [ 8 ], which is associated with slower disease progression [ 17 ], it is reasonable to hypothesize that HLA-A*23 is associated with slower disease progression, potentially mediated by both lower VRC and ARS. However, elaborate studies are warranted to clearly elucidate associations between HLA-A*23, a common allele in some sub-Saharan African settings [ 18 ], with disease progression, while controlling for confounding factors. Further exploration of the influence and mechanisms of action of HLA-A*23 on the early immune responses and subsequent long-term effects could enable the identification of peptides for priming immune responses in attempts to reduce the inflammatory burden and mitigate disease progression.…”
Section: Discussionmentioning
confidence: 99%